Dual sensory impairments in companion dogs: Prevalence and relationship to cognitive impairment. - Ryan G Hopper; Rachel B Bromberg; Michele M Salzman; Kyle D Peterson; Callie Rogers; Starr Cameron; Freya M Mowat (PLoS ONE)
Purpose Many older dogs (Canis lupus familiaris) develop cognitive impairment. Dog owners often describe impairments in multiple sensory functions, yet the relationships between sensory and cognitive function in older dogs is not well understood. Methods We performed assessments of dog vision and hearing, both clinically (n = 91, electroretinography and brainstem auditory evoked potential) and via validated questionnaire (n = 238). We determined prevalence of sole and dual hearing/vision impairments in younger (<8 years) and older (≥8 years) dogs. Impairment cutoffs were determined using data from young dogs. We assessed the relationships between questionnaire-assessed vision and/or hearing impairments and cognitive impairment using logistic regression. Results Younger and older dog groups had similar distributions of sex and purebred/mixed breed status. Sex had no relationship to prevalence of sensory impairments. Older dogs had higher prevalence of hearing, vision, and dual sensory impairments, assessed both clinically and by questionnaire (P<0.001), and cognitive impairment assessed by questionnaire (P<0.001). Dogs had higher prevalence of reported cognitive impairment when owners reported dual vision and hearing impairments (79-94%, versus 25-27% in dogs with no sensory impairments), which was most consistent in dogs aged ≥8 years. In these older dogs, dual vision/hearing impairments were associated with a significantly increased risk of cognitive impairment (1.8-2.0 odds ratio). Conclusion Dogs aged ≥8 years are at higher risk for dual hearing/vision impairments and associated cognitive impairments. The causal relationship between these impairments is not defined, but clinical consideration of these multimorbidity risks should be made in older dogs.